The Historical Development of Local Government Administration and Its Contemporary Realities in Nigeria - Etebom John Monday; Junior Hendri Wijaya (TheJournalish: Social and Government, 2022)
Local government is the government at the grassroots closest to the people. It is the tier of government administration that coordinates the activities of citizens at the local community levels. Local government as a concept of government existed long before the arrival of the colonialists. There were forms of local government administrations in Nigeria before colonial rule. During colonialism, the British's indirect rule system was built upon existing local administrations in Nigeria. However, the story is not the same for local government administration regarding structure and organization in the country today. The study x-rayed the various phases and eras of local government development in Nigeria. It further analyzed the present realities of local administration in the country. The study employed a qualitative approach. The qualitative data were generated from interview responses from relevant stakeholders (such as Traditional leaders and senior local government administrative staff). Also, data were gathered from existing relevant literature. Data collected were analyzed using the context analysis method. The study revealed that local government administration in Nigeria has passed through torturous phases. It identified the lack of local government autonomy amongst others as the main challenge bedeviling its development in the country. The study concluded with recommendations to reposition local government for effective service delivery as Nigeria's third tier of government.